The General Theory of Metadynamics Systemicity - BLANC, Jean-Jacques (Proceedings of the 57th Annual Meeting of the ISSS - 2013 HaiPhong, Vietnam, 2014)
The General Theory of Systemicity is being published - part after part since 2004 - from after the application of “The Bioethism Transdisciplinary Paradigm” that the author J.-J. Blanc developed since 1996. Made from an extensive research on "Systems science" that induced to his developing a new systemic paradigm, it was termed as a transdisciplinary approach to "Living systems" he named “The Bioethism”. A paradigm that is meant to support the acquisition of a large understanding on living systems' as naturally structuring and behaving for survival while adapting to their milieu. The "Cosmo-planetary and terrestrial metadynamics systemicity”, the “Life’s metadynamics systemicity”, and the "Biological survival metadynamics systemicity" processes are the core of the General Theory, which, resulting from a large research and approach of the whole set of universal metadynamics and their retroactivity, shows their interrelationship and interdependency. The systemicity of their atomic and molecular cycles has made and sustains both cosmic systems and Life on planet Earth. As to exist, living creatures replicate and evolve within global, glocal and local permanently changing endogen milieu and external environmental ecosystems. The Universe Cosmo-planetary gigadynamics and metadynamics systemicity have participated in the Sun and its planets to form, and particularly Earth orbiting around it on a right “habitable green zone”. The General Theory shows the close links between Cosmo-planetary and terrestrial meta-dynamics systemicity, its forces, fluxes and moves cycles that made Life to have happened and thriven. From proto-organisms to humans, their individualities, social traits and behavioral statuses have accounted for the biodiversity of species developing or getting extinct over billions of years. For example, when the Earth became a "snowball" from a nearly total glaciation (-600 Mo/y), the survival of some bacteria and micro-organisms escaping the drastic extinction of most species, conversely boosted up an extraordinary explosion of marine species bearing quite new functions (- 545Mo/y), that after volcanism reheated the planet from the systemicity of interrelated terrestrial and cosmic metadynamics. These metadynamics are the main physicochemical cosmic, galactic, stellar, planetary and terrestrial feedback processing atoms to participate in forming matter and cosmic objects (nebulae, baby stars, stars and planets), within a molecular world as originated from after the “Big Bang”. Influenced with a certain number of forces, and going towards specific directions in the environment, Life as a whole is confronted with gravitation, electromagnetism, chemical and physical phenomena…, particularly temperature and the “thermodynamics of entropy”, all being forces and fluxes which driving diversity is concomitant. Furthermore, Life is confronted with the driving of terrestrial dynamic cycles of water, minerals, and climates which currents drive ecosystems metabolism. Among drivers are the coalescence, conjunction, co-evolution, convergence, symbiosis, percolation, phase transition and threshold output, neighborhood adaptation. Then feedback drives universal atomic, molecular and physicochemical worlds permanently provoking the evolution of the several metadynamics systemicity cycles. The specific bonds and traits of structures and behaviors as well as the evolution trends of “surviving living creatures” require some knowledge about actions-reactions (drivers) with ago-antagonistic signals and stimuli emerging from their ecosystemic and socio-systemic metabolism and environmental conditions. Since resulting in some sort of a confrontation between the body milieu and the natural environment, the narration and treatment of a general information refers to the fundamental “survival metadynamics systemicity" and “its drivers” like “symbiosis” and “feedback” as processing stimuli and signals to sustain their metabolism balance from both internal and external changing conditions. Part five of this theory only describes some drivers: symbiosis, coalescence, convergence and synergy, percolation, phase transition, threshold output, feedback… that permanently influence the systemicity of cosmic matter, objects and things interacting among the universal networks of the 3D worlds. Feedback driving the survival metadynamics systemicity sustains “the atomic and molecular cycles from cradle to grave”.